(untitled) (Research, Society and Development, 2024)
The general objective of this study is to synthesize the best scientific evidence on the benefits of ozonated autohemotherapy in different clinical contexts, describing its effectiveness and safety. This study is an Integrative Literature Review (RIL). The searches were carried out in the databases Scielo (Scientific Electronic Library Online), Lilacs (Latin American and Caribbean Literature in Health Sciences), PubMed and the Capes periodical portal. The studies analyzed highlight the applicability and versatility of ozone therapy in different medical conditions and contexts. They explore its use in specific medical conditions, such as osteonecrosis, osteoarthrosis and post-radiotherapy tissue necrosis, as well as its application in aesthetics, immunology and treatment of fibrous edema geloid. And, they focus on treating skin conditions. Finally, a study emphasizes the need for legal regulation to guarantee the safety and effectiveness of ozone therapy. These studies collectively reinforce the therapeutic potential and versatility of ozone therapy in diverse healthcare contexts. Through the analysis of existing scientific literature, it was possible to compile data on the effects of ozonized autohemotherapy on the body’s immune response and identify the mechanisms through which this therapy can influence immunological activity. Furthermore, the analysis of the clinical results of patients undergoing ozonated autohemotherapy allowed a comparison with control groups that did not receive such intervention, contributing to the determination of the effectiveness of the therapy in different health conditions.